PENGKEMASAN PAKET WISATA TRACKING DENGAN KONSEP TRI HITA KARANA DI DESA MUNDUK-BULELENG - I Nyoman Surya Maha Putra; I Wayan Suardana; I Putu Sudana (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2017)
Munduk village is located in the district of Banjar, Buleleng regency, which has a variety of attractions that can be developed. The purpose of this study was to determine the potential of tourism and packaging of tracking package tour with the concept of Tri Hita Karana in Munduk Village, Buleleng. The informants technique used in this research is purposive sampling. The informants in this research consisted of The chief of Munduk village, leaders community, and local guides. The analysis data technique used is descriptive qualitative. The results of this research indicated that Munduk has tourism potential in terms of natural landscapes, arts, local community trust, habits of the population, and historic buildings. Based on this potential, Tracking activities in Munduk village will packed into a tour packages by applying the concept of Tri Hita Karana. The tracking tour packages is divided into two options, namely Munduk Waterfall Tracking and Munduk Rice Field Tracking.